Concept and behaviour of all-steel miniature bar-typed structural fuses with torsional effect. (January 2020) - Guan, Dongzhi; Yang, Sen; Liu, Yan; Ge, Hanbin; Guo, Zhengxing
Abstract: Structural fuses installed in buildings and bridges have become an appropriate option to protect structural elements from earthquake attacks. A miniature bar-typed structural fuse (MBSF) is introduced in this paper, consisting of a confining tube, a central core, and several nuts. The cross section of the yielding portion in the central core is shaped as a quasi-triangle comprising three remaining arcs and three cut straight lines. Four specimens were axially tested under either symmetric or asymmetric cyclic loading histories, which were also analyzed numerically by finite element (FE) models. A theoretical model was proposed to analyze the MBSF. The results show that the specimens exhibit satisfactory seismic performance under the two loading histories. The single buckling half-wave segment deforms with torsional angles at the ends with a high possibility. The proposed analytical model considering the torsional effect can be used to evaluate the maximum nominal compressive stress of the MBSF. Highlights: An all-steel miniature bar-typed structural fuse (MBSF) was investigated. MBSF has satisfactory seismic performance under both the asymmetric and symmetric loading histories. The second moment of area for the quasi-triangular cross section in MBSF remains the same in different directions. The single buckling half-wave segment of MBSF might deform with torsional angles at the both ends. The proposed theoretical model considering torsional effects matches well with the experimental results.